Perancangan Perangkat Lunak Sistem Tata Kelola Kegiatan Cleaning Dalam Perencanaan Peminjaman Dan Penyewaan Petikemas EMKL - Chaeril Tri Seprians; Sean Coonery Sumarta (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2021)
The activity of container cleaning service is one of the service activities in PT Kaltim Kariangau Terminal which aims to assist containers, this activity was one of the activities that was provided for Shipping Loading Expedition (EMKL) before EMKL carried out the delivery of its Customer goods. To carry out freight forwarding and container cleaning activities, EMKL borrows containers first from shipping companies because shipping is an institution that has rights related to containers to be leased to EMKL. To minimize the cost of lending to shipping parties and improve the accuracy of shipping goods customers need accurate data, where this data can be obtained from cleaning activities at PT Kaltim Kariangau Terminal. But at PT The Karingau East Kalimantan Terminal itself also does not have a system that supports the cleaning service itself. EMKL cannot increase the accuracy of the time in shipping the Customer's goods and also in the reduction of borrowing costs for containers. In designing the method to be used is the Waterfall Method using this method for each person that will be done before proceeding to the next stage. The results of this study are systems that support all activities in PT Kaltim Kariangau Terminal which will process all the processes that occur during the ongoing cleaning process EMKL can use the data in conducting customer goods planning systematically and can be used by the customer as a result of planning the delivery of the goods.